LA INCONSTITUCIONALIDAD DE LA CAUCIÓN, CONTEMPLADA EN EL ARTICULO 27 DEL CÓDIGO ORGÁNICO GENERAL DE PROCESOS - VALDIVIESO ESPINOZA, TATIANA NOEMÍ (2018)
The present research project is born from the need of studying from the legal aspect, and even more, of constitutionality, the application of the rules of procedure of the new legal system, which is contained in the new Organic Code General of processes. In virtue of what development the problematic of the issue raised by outlining the constitutional mandates that contract in the first place to the mandate contained in article 427 of the Constitution of the Republic of Ecuador, same that in its relevant part sorts: "The constitutional rules shall be interpreted by the wording that best suits the Constitution in its entirety ..." ; integrality that part of the principle that all rights enshrined in the Constitution are fundamental, and which do not allow to establish any kind of hierarchy between them, to such an extent that it can be established that some are more important than others. It is inconceivable to think of a dignified life if these rights are violated by procedural rules that violate the access to justice, which goes against specific rule, as set out in article 75 of the Constitution of the Republic that sorts: "Every person has the right to free access to justice and to the effective protection, impartial and expeditious manner of their rights and interests, subject to the principles of immediacy and clarity; in no case will be in helplessness."; 6 even more, within the same body we find that the numeral 4 of article 168 of the same constitutional body ordered so imperative: "access to the administration of justice will be free" Accordingly, Like any right enshrined in the Constitution, the right to justice requires a system of guarantees which allows for its full exercise, because this collapses to the State to create tracks materials and the legal conditions necessary to ensure that the validity of the same without obstacles that interfere with the equality and thus have an effective exercise of the rights that are justiciable; In reason of these assertions article 169 of the Constitution of the Republic establishes that: "the procedural system is a means for the realization of justice" , therefore, the surety is contained in article 27 of the Organic Code of General Processes, same that in its contents sorts: "presented the Demand, within the term of three days, or the judge shall set a bond of between one and three unified basic wages of a worker in general, who shall be appropriated by the or the actor. Without this requirement, the demand will not be qualified and available your file."; and in this way sets a requirement for admissibility, same as attentive with free access to the justice system and its gratuity, consequently it is recognized that these rights have so that every person can make you use of the defense in conditions of equality and legal certainty, holding that the right to equality "…must be real and non-formal, seeking to ensure that the equality of persons is realized in facts that are tangible, eliminating the gaps between the norm and reality, 7 allowing persons who consider that their rights have been violated, threatened or denied, can obtain a prescribed solution In the legal system, without requiring the payment of a filing fee whatsoever for the recognition of the same